The Mediating Role of Distributive Fairness in the Relationship Between Performance-Based Pay, Career Incentive Organizational Benefits and Employee Performance - Ismail, Abdussalaam Iyanda (2014)
This work aims to examine the relationship between performance-based pay, career incentives, organizational benefits and employee performance. It also aims to test the mediating role of distributive fairness in these relationships. Nigerian working class students in Universiti Utara Malaysia (UUM) were sampled. A total number of 140 respondents were given questionnaires to fill but 116 questionnaires were good enough for analysis. Descriptive analysis, correlation analysis and hierarchical regression analysis were used to analyze data and to test the hypotheses. The overall findings indicated that there are relationships between performance-based pay, career incentives, organizational benefits and employee performance. Moreover, it was also found that distributive fairness partially mediated the relationships between performance-based pay, career incentives, organizational benefits and employee performance. This study is limited in the aspect of various organizational characteristics such as type, ownership, and size and the aspects of personal characteristics such as gender, position, length of service, and qualification. Therefore, future researches should examine the various aspects of organizational characteristics and personal characteristics in relation to performance-based pay, career incentives and organizational benefits within organizations. Organizations thrive through the instrumentality of people because they possess the required skills, knowledge and competencies needed for the execution of organizational strategy and planning. Hence, organizations should entrench a competitive total remuneration package that consists of properly-handled performance-based pay system, career incentives and various organizational benefits based on the principle of distributive fairness. In addition, management should build up an effective pay design and management systems in organizations. Openness in communication and employee participation in the pay design and management help in achieving this goal